Asymmetrical Contribution of Brain Structures to Treatment-Resistant Depression As Illustrated by Effects of Right Subgenual Cingulum Stimulation - Guinjoan, Salvador Martín (2010)
Major depressive disorder is one of the most common psychiatric disorders, with a worldwide lifetime prevalence rate of 10%-20% in women and a slightly lower rate in men. While many patients are successfully treated using established therapeutic strategies, a significant percentage of patients fail to respond. This report describes the successful recovery of a previously treatment-resistant patient following right unilateral deep brain stimulation of Brodmann´s area 25. Current therapeutic approaches to treatment-resistant patients are reviewed in the context of this case with an emphasis on the role of the right and left hemispheres in mediating disease pathogenesis and clinical recovery.